Temporal and spatial variability in the life-history of the surf clam Donax deltoides: Influences of density dependent processes. (5th February 2021) - Ferguson, Greg J.; Hooper, Graham; Mayfield, Stephen
Abstract: This study aimed to determine if population dynamics and demography of the sandy beach bivalve, Donax deltoides, varied under different levels of biomass. To achieve this, population parameters for D. deltoides in south-eastern Australia were compared across a range of spatial and temporal scales during periods of low-moderate and high relative biomass. Estimates of relative harvestable biomass were lower in 2008–12 (2.3 ± 0.03 kg m 2 ), compared to 2013–17 (3.7 ± 0.11 kg m 2 ; P < 0.001), and also differed among years ( P < 0.001), and 3 month periods within years ( P < 0.001), although there was no difference between repeated days. Relative biomass also varied across six, 10 km sections of the 60 km study area with the central third of the study area relatively stable among years and the north-western and south-eastern thirds more variable. Mean and maximum length of D. deltoides varied across temporal and spatial scales similar to those of relative biomass. Growth performance in 2008–12 ( φ' = 3.32) was higher than that in 2013–17, ( φ' = 2.99) although the difference was not statistically detectable ( P > 0.05). Instantaneous mortality ( Z ) also differed between 2008–12 and 2013–17 ( P < 0.05). High relative biomass in 2013–17, following successive years of successful recruitment, occurred contemporaneously with decreased growth performance and likely suppression of subsequent recruitment, suggesting possible density dependence and growth over-compensation. Reduced growth rates under higher relative biomass imply that attainment of sexual maturity may be delayed, or alternatively maturity may occur at a smaller size, both of which have implications for individual lifetime egg production. Improved understanding of population dynamics, demography and exploitation patterns across a range of temporal and spatial scales has important implications for implementation of spatially explicit management. Highlights: Donax deltoides has high spatial and temporal variability in size, recruitment, and growth. Demographic variability occurs across a wide range of temporal and spatial scales. Reduced growth and recruitment occurred at high levels of biomass suggesting density effects. Density dependent growth has implications for lifetime egg production. Understanding demography and population dynamics at a range of temporal and spatial scales is important for management.